Political correctness and linguistic creativity in the job market. How much do they (mis) inform? - Delekta, Ilona (Revista Internacional de Organizaciones, 2020)
The article examines how political correctness (PC) affects work-related lexis. A particular focus is put on English bizspeak that aims to fulfil PC demands by using creative vocabulary and euphemisms to motivate employees, stimulate their creativity, and win or keep customers. A brief theoretical outline is followed by an analysis based on authentic material. The results show that such colourful language may contradict PC postulates and impede effective communication.